The Effect of Pressure, Opportunity, and Rationalization on Financial Reporting Fraud: Evidence from Manufacturing Companies Listed on the Indonesia Stock Exchange (2020–2024) - Egta Ayu Fadhillah Sugiarto; Zaharuddin Zaharuddin; Supriyadi Supriyadi (Global Academy of Multidisciplinary Studies, 2026)
Purpose: This study investigates the influence of pressure, opportunity, and rationalization, the three elements of the fraud triangle, on financial reporting fraud among manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2020–2024. Research Methodology: A quantitative descriptive-verification design was used with secondary data from published annual financial reports. Pressure was proxied by leverage ratio, opportunity by changes in accounts receivable, and rationalization by auditor turnover (DCHANGE). Fraudulent financial reporting was measured using the Beneish M-Score. A sample of 67 companies (335 firm-year observations) was selected using proportional stratified sampling. Multiple linear regression analysis was applied. Results: The results showed that opportunity significantly affected financial reporting fraud (? = 0.891, p < 0.001), while pressure and rationalization were insignificant. Together, the three factors explained some variation in fraud risk (F = 7.812, p < 0.001, R² = 0.066). Conclusions: Opportunities, particularly changes in accounts receivable, were found to significantly influence financial reporting fraud. Pressure and rationalization, though insignificant individually, explained some variation in fraud risk. Internal controls on receivables management are critical. Further research is needed to explore additional variables and alternative fraud-measurement models. Limitations: This study focuses only on the manufacturing sector with a five-year observation period, and the DCHANGE proxy for rationalization may underestimate its true effect. Contributions: The findings offer empirical evidence on the roles of fraud triangle elements in Indonesian manufacturing, providing insights for regulators, auditors, and corporate governance practitioners in fraud prevention.